1996
DOI: 10.1152/jn.1996.76.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Membrane properties and synaptic currents evoked in CA1 interneuron subtypes in rat hippocampal slices

Abstract: 1. Intrinsic membrane properties and pharmacologically isolated excitatory and inhibitory postsynaptic currents (EPSCs and IPSCs, respectively) were characterized with the use of whole cell current- and voltage-clamp recordings, in combination with biocytin labeling, in different subtypes of CA1 interneurons and pyramidal cells in rat hippocampal slices. 2. Three classes of interneurons were selected on the basis of their soma location in the CA1 region: 1) in stratum (str.) oriens near the alveus (O/A), 2) ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 0 publications
6
39
1
Order By: Relevance
“…The total surface area is 2.21U10 34 cm 2 . The input resistance of the cell is V290 M6 which approximately matches values measured experimentally (Morin et al, 1996). The calculated membrane time constant is V6 ms which also approximates experimental data (Lacaille et al, 1987;Lacaille and Williams, 1990).…”
Section: Multi-compartment Interneuron Modelsupporting
confidence: 83%
See 1 more Smart Citation
“…The total surface area is 2.21U10 34 cm 2 . The input resistance of the cell is V290 M6 which approximately matches values measured experimentally (Morin et al, 1996). The calculated membrane time constant is V6 ms which also approximates experimental data (Lacaille et al, 1987;Lacaille and Williams, 1990).…”
Section: Multi-compartment Interneuron Modelsupporting
confidence: 83%
“…Passive properties are chosen to approximate an oriens/alveus (O/A) hippocampal interneuron. The surface area for this model is taken from the literature (Morin et al, 1996) and the model consists of an axon, a soma and a dendrite (10 segments). The total surface area is 2.21U10 34 cm 2 .…”
Section: Multi-compartment Interneuron Modelmentioning
confidence: 99%
“…Thurbon et al (1994) and Morin et al (1996) found that ô0 of CA1 non-pyramidal cells was 25-30 ms, while in dentate gyrus basket cells ô0 was less than 20 ms (Mott et al 1997). A similar relationship exists for CA3 pyramidal neurones and other principal cells of the hippocampal formation (Spruston & Johnston, 1992).…”
Section: Discussion Passive Properties Of Hippocampal Ca3 Interneuronesmentioning
confidence: 99%
“…Such data are not available for morphologically identified hippocampal interneurons. Some previous studies have examined the inhibition in interneurons using sharp microelectrodes or have recorded evoked IPSCs (Misgeld and Frotscher, 1986;Lacaille et al, 1987;Lacaille and Schwartzkroin, 1988a,b;Lacaille, 1991;Williams et al, 1994;Morin et al, 1996). These studies, however, lacked proper morphological identification of the recorded cells and may have failed to achieve the high resolution afforded by patch-clamp techniques that is necessary to reveal small amplitude synaptic activity (Soltesz and Mody, 1994).…”
Section: Abstract: Hippocampus; Nonpyramidal Cells; Intracellular Lamentioning
confidence: 99%